Using augmented reality video in enhancing masonry and roof component comprehension for construction management students. Issue 6 (21st November 2016) - Shanbari, Hamzah; Blinn, Nathan; Issa, Raja R.A.
Abstract : Purpose: New methods to introduce topics in classrooms are needed to enhance the construction management educational experience. One of these new methods is showing real time videos that highlight the various elements of concern in the classroom lecture. The purpose of this paper is to use augmented reality technology (ART) and a layer of artificial visualizations to simulate the environmental context and spatio-temporal constraints of various construction processes. The superimposition of images serves as an instructional mechanism to virtually incorporate jobsite experiences into classrooms. This enhancement of spatio-temporal constraints enables learners to visualize context and hidden processes otherwise unattainable through traditional classroom lectures. Design/methodology/approach: A significantly improved perception of reality is created through the combination of the learners' ability to understand the complexity of construction products (e.g. assemblies) and associated jobsite processes by viewing the real environment augmented with computer-generated information layers. Findings: Testing the ART video in a classroom with undergraduate construction management students showed that students who were exposed to the ART video were able to remember and identify the highlighted elements in the corresponding assembly more effectively than those who were not. Originality/value: ART is a valuable tool in enhancing classroom learning and gives educators a teaching advantage when they combine traditional classroom lectures with ART enabled media.